Pengaruh Kompetensi Auditor Independensi Auditor Dan Etika Profesi Terhadap Laporan Audit: Sebuah Literatur Review - Fadhil, Naufan; Kuntadi, Cris (Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
An audit report plays an important role as a means of professional coordination between auditors and stakeholders in assessing an entity’s financial statements. The validity of the information contained in the audit report contributes to building trust among investors, creditors, regulators, and other parties who have the authority to make economic decisions. Therefore, the audit report cannot be separated from the competence of the auditor who prepares it.The purpose of this article is to theoretically analyze the influence of auditor competence, auditor independence, and professional ethics on audit quality through a literature review study. The results of this study indicate that, in general, competence, independence, and professional ethics are interrelated and constitute important factors in producing independent and accurate audit reports. Consistent application of Auditor Competence, Auditor Independence, and Professional Ethics is expected to improve the quality of audit reports and enhance the confidence of stakeholders in the financial information presented.